Bartter Syndrome: A Case Report - Yayik Supriyani; Deka Viotra; Putri Deas Hadilofyani (HM Publisher, 2023)
Background: Bartter's syndrome refers to a group of genetic disorders that affect the renal tubular system, which is responsible for reabsorbing various substances such as sodium, potassium, and chloride from the urine into the blood. This study aimed to present a clinical case related to Bartter syndrome. Case presentation: A 52-year-old male patient in the internal medicine department of Dr. M. Djamil General Hospital Padang with the main complaint of weakness in both legs increasing since 1 day ago. On laboratory examination, the patient found potassium 1.7 mmol/L, indicating hypokalemia. Renal function examination showed normal kidney function. Examination of blood gas analysis showed results of metabolic alkalosis. Examination of urine potassium obtained potassium levels of 22 mmol/day, urine osmolarity of 140 mOsm/kgH2O at serum osmolarity of 274 mOsm/kgH2O, with TTKG (transtubular potassium gradient) = 28. The patient was diagnosed with Bartter syndrome. Treatment is carried out by administering KSR tablets 3x600 mg orally while monitoring electrolytes regularly. Conclusion: This patient has hypokalemia, metabolic alkalosis, normal magnesium and calcium, and hypercalciuria. This patient is diagnosed with Bartter syndrome.